UTILIZATION OF BROILER CHICKEN BYPRODUCT (ABDOMINAL FAT) AS A WOUND HEALING AGENT - Muhammad Yunus; Hartina Beddu; Nuzul Hidayat (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Traditional medicine is of sufficient concern to continue to be developed and strive to become part of formal medicine in Indonesia, in line with the